2014
DOI: 10.1155/2014/542606
|View full text |Cite
|
Sign up to set email alerts
|

New Product Development in an Emerging Economy: Analysing the Role of Supplier Involvement Practices by Using Bayesian Markov Chain Monte Carlo Technique

Abstract: The research question is whether the positive relationship found between supplier involvement practices and new product development performances in developed economies also holds in emerging economies. The role of supplier involvement practices in new product development performance is yet to be substantially investigated in the emerging economies (other than China). This premise was examined by distributing a survey instrument (Jayaram’s (2008) published survey instrument that has been utilised in developed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Otherwise, we cannot, in standard approach, determine the sample covariance matrix. Therefore, to overcome this issue, use of Bayesian structural equation modeling (BSEM), as a representative of semi-parametric modeling, is offered by so many researchers [27]. BSEM, for the parameters of interest, allows the researchers to apply the prior information for updating the current information.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, we cannot, in standard approach, determine the sample covariance matrix. Therefore, to overcome this issue, use of Bayesian structural equation modeling (BSEM), as a representative of semi-parametric modeling, is offered by so many researchers [27]. BSEM, for the parameters of interest, allows the researchers to apply the prior information for updating the current information.…”
Section: Introductionmentioning
confidence: 99%
“…While in the creation of knowledge of competitive markets, supply chain engagement becomes an efficient, operational and interrelated process of information to organizations. As in Feng & Wang (2013) research, supply engagement is related to customer and supplier engagement positively, but it can improve performance (Kanapathy, Khong, & Dekkers, 2014;Feng & Zhao, 2014). We hope this discussion can be a future reference to further research in the supply chain's engagement to business performance especially in small and medium-sized firms that have implemented business in two marketing systems (offline and online).…”
Section: Contribution To the Supply Chain Literaturementioning
confidence: 80%
“…Suppliers' contributions to solutions that increase process productivity and improve manufacturability allow for cost reduction (Mcivor & Humphreys, 2004;Luo et al, 2010). Proving these points, Kanapathy et al (2014) conducted a survey with 146 manufacturing companies in an emerging economy and demonstrated that supplier involvement has a significantly positive impact on NPD project performance in terms of quality objectives, design objectives, cost objectives and "time-to-market" objectives. Dekkers et al (2013) address the interface between product design and manufacturing and highlight the importance of supplier involvement and articulation through information and communication technologies (ICT), both hardware and software.…”
Section: Early Supplier Involvementmentioning
confidence: 99%
“…In addition to CAD systems, other important systems that, together with CAD, form the concept of Computer-Integrated Manufacturing (CIM) are the Computer-Aided Manufacturing (CAM) and Computer-Aided Engineering (CAE). These systems, when mainly used together with data shared by SC members, provide a significant competitiveness increase for involved companies (Figueiredo & Romeiro Filho, 2011) and can truly represent a shift paradigm in NPD (Kanapathy et al, 2014).…”
Section: Information System In New Product Developmentmentioning
confidence: 99%